IMPLANTAÇÃO DE UM SOFTWARE DE SISTEMA DE GESTÃO DIGITAL PÚBLICA INTEGRADA DE DOCUMENTOS E PROCESSOS: AS PERCEPÇÕES DOS SERVIDORES DO MUNICÍPIO DE PANCAS - ES. (REMUNOM, 2023)
The public management without paper it is a trend increasingly stronger in various government spheres, in the function of the advantages that it offers in terms of efficiency, agility, transparency and resource saving, which can improve the quality of services provided to citizens, searching about a implementation of one software of system of digital management integrated documents and processes: the server perceptions of the municipality of Pancas-ES, in order to discuss the implementation of a digital system for Integrated Public Management of documents and processes. For now, it is necessary to verify the perception that users had regarding the implementation of an innovative methodology in the use of processes and documents in digital format, investigate the impact caused by the implementation of the system in the economy direct financial resources and analyze the perception of servers regarding productivity gains, efficiency and effectiveness in Public Pancas Management after the implementation of the Digital Process. Applied, then, a survey research, descriptive, of an applied nature, with a qualitative approach. In this case, check it out the results applied of search with Pancas servers indicate a positive perception in relation to the E-GPI system, with a high level of trust and usability. There was a significant improvement in municipal management after implementation of the system, with reduction of direct costs, processing time of processes and positive impacts on the work routine, what imposes the constation that in this way, such results point to a contribution to more efficient and sustainable management.